Toward nanofluidics‐based mass spectrometry for exploring the unknown complex and heterogeneous subcellular worlds. Issue 1 (28th December 2022) - Chantipmanee, Nattapong; Xu, Yan
Abstract: Exploring unknown matter in an ultrasmall volume object, such as unknown subcellular matter in a single cell, requires an analytical technique that identifies unknown matter in terms of molecular structures and properties. Mass spectrometry is considered one of the best techniques for such analyses because it can identify unknown matter according to its mass‐to‐charge ratio. However, the use of mass spectrometry to identify unknown substances in such a small world has been greatly impeded due to the lack of tools to sample complex and heterogeneous analytes with ultrasmall volumes of the picoliter order, which is the volume order of a mammalian cell. We believe that nanofluidics would be an ideal tool to resolve this critical issue owing to its ability to sample such fluid samples with ultrasmall volumes ranging from the picoliter to zeptoliter order. Thus, the integration of such nanofluidic features into mass spectrometers would open up future avenues for the potential of mass spectrometry to explore unknown subcellular matter at a nano scale. In this perspective, we first discuss the applicability of microfluidics/nanofluidics to mass spectrometry, then address critical issues toward nanofluidics‐based mass spectrometry, and finally depict a personal outlook on the future of this field to resolve challenges on global and universal scales. Abstract : In this perspective, critical issues and grand challenges toward nanofluidics‐based mass spectrometry are discussed and a personal outlook on the future of this field is depicted. We believe that nanofluidics‐based mass spectrometry will grow to be a powerful analytical tool to resolve critical issues on not only the microscopic scale but also global and universal scales.